1996
DOI: 10.1172/jci118421
|View full text |Cite
|
Sign up to set email alerts
|

Energy-ubiquitin-dependent muscle proteolysis during sepsis in rats is regulated by glucocorticoids.

Abstract: Recent studies suggest that sepsis-induced increase in muscle proteolysis mainly reflects energy-ubiquitin-dependent protein breakdown. We tested the hypothesis that glucocorticoids activate the energy-ubiquitin-dependent proteolytic pathway in skeletal muscle during sepsis. Rats underwent induction of sepsis by cecal ligation and puncture or were sham-operated and muscle protein breakdown rates were measured 16 h later. The glucocorticoid receptor antagonist RU 38486 or vehicle was administered to groups of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
198
4
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(228 citation statements)
references
References 35 publications
23
198
4
3
Order By: Relevance
“…In many other conditions with increased muscle proteolysis (e.g. sepsis, trauma, cancer, acidosis, denervation atrophy), it is the ubiquitinproteasome pathway rather than lysosomal proteolysis that is increased (Attaix et al, 1994;Llovera et al, 1995;Medina et al, 1995;Bailey et al, 1996;Tiao et al, 1996). It is likely that amino acids primarily inhibit lysosomal proteolysis in muscle (Wing & Goldberg, 1993).…”
Section: Control By Amino Acids and Hormonesmentioning
confidence: 99%
“…In many other conditions with increased muscle proteolysis (e.g. sepsis, trauma, cancer, acidosis, denervation atrophy), it is the ubiquitinproteasome pathway rather than lysosomal proteolysis that is increased (Attaix et al, 1994;Llovera et al, 1995;Medina et al, 1995;Bailey et al, 1996;Tiao et al, 1996). It is likely that amino acids primarily inhibit lysosomal proteolysis in muscle (Wing & Goldberg, 1993).…”
Section: Control By Amino Acids and Hormonesmentioning
confidence: 99%
“…Furthermore, Hasselgren and Fischer [12] showed that dexamethasone (DEX) stimulates proteasome-and calcium-dependent proteolysis in the same cells [13]. Other studies [12,14] confirmed that sepsis induces proteolysis by activation of the ubiquitin-proteasome system, and that this activation was regulated by GCs [15]. These findings represent a unique situation where the increased GC levels described with sepsis are associated with upregulated GR levels in muscle cells, in contrast to most cells, where increased GCs levels are associated with GR downregulation.…”
Section: Introductionmentioning
confidence: 97%
“…Glucocorticoids increase protein catabolism by opposing the suppression of the transcription of the proteasome C3 a-subunit by nuclear factor-kB (NF-kB), by antagonising the interaction of NF-kB with an NF-kB response element in the C3 subunit promoter region (Du et al, 2000). Also physiological levels of glucocorticoids are necessary, but not sufficient for the catabolic response in rats with metabolic acidosis (Price et al, 1994), starvation (Wing and Goldberg, 1993) and sepsis (Tiao et al, 1996). However, chronic excessive glucocorticoid production, as occurs in Cushing's syndrome is not associated with an increased mRNA for ubiquitin, the ubiquitin-conjugating enzyme, E2 14k , or proteasome subunits (Ralliere et al, 1997), suggesting that other factors may be involved.…”
mentioning
confidence: 99%